Doc : memories from a life in public service - Bowen, Otis R. (Indiana University Press, 2000)
"He was affectionately known by his constituents as "Doc," and may well have been the most popular governor in Indiana's history. Now "Doc" Bowen has given us his story. He writes in rich detail of how hard work and persistence got him into and through medical school, and how his commitment to serving people led him early on to become a beloved family physician in Bremen, then later a respected state legislator and legislative leader in Indiana, and ultimately governor of the state."